2009
DOI: 10.1002/hyp.7219
|View full text |Cite
|
Sign up to set email alerts
|

Simulating short‐circuiting flow in a constructed wetland: the implications of bathymetry and vegetation effects

Abstract: Abstract:Short-circuiting flow, commonly experienced in many constructed wetlands, reduces hydraulic retention times in unit wetland cells and decreases the treatment efficiency. A two-dimensional (2-D), physically based, distributed modelling approach was used to systematically address the effects of bathymetry and vegetation on short-circuiting flow, which previously have been neglected or lumped in one-dimensional wetland flow models. In this study, a 2-D transient hydrodynamics with advectiondispersion mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 40 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…However, published literature reveals many studies where the latter comparisons are not considered (Wörman and Kronnäs, 2005;Wang and Jawitz, 2006;Min & Wise, 2009;Keefe et al, 2010). For the present study, the consequence of such comparisons showed that Gauss-based parameter values, especially from EVWs, were generally not reliable (Table A in Consequently, these N-values were considered as unreliable compared to the ones based on measured data and also compared to the other modelled N-values.…”
Section: Rtd Characteristics and Data Analysis Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, published literature reveals many studies where the latter comparisons are not considered (Wörman and Kronnäs, 2005;Wang and Jawitz, 2006;Min & Wise, 2009;Keefe et al, 2010). For the present study, the consequence of such comparisons showed that Gauss-based parameter values, especially from EVWs, were generally not reliable (Table A in Consequently, these N-values were considered as unreliable compared to the ones based on measured data and also compared to the other modelled N-values.…”
Section: Rtd Characteristics and Data Analysis Methodsmentioning
confidence: 86%
“…Instead, the focus of most published wetland hydraulic studies has been comparing effects on wetland hydraulics caused by different vegetation layouts (Persson et al, 1999;Dal Cin and Persson 2000;Jenkins and Greenway, 2005) or vegetation heterogeneity levels within the same vegetation type (Wörman and Kronnäs, 2005;Kjellin et al, 2007;Min and Wise, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A number of additional studies have confirmed this finding [16][17][18]. The hydraulics of ponds and wetlands can generally be evaluated through mathematical modeling [19,20] and tracer experiments [21,22]. This study investigated the flow hydrodynamics, residence time distribution, and hydraulic performance of a treatment pond using tracer experiments and mathematical modeling.…”
Section: Introductionmentioning
confidence: 78%
“…A common phenomenon that is observed in natural and constructed wetlands is short-circuiting of flow and formation of stagnant zones that are only indirectly available to the inflow waters (Min and Wise 2009). Such stagnant zones can offset treatment effectiveness of wetlands by reducing active volume and consequently shortening the hydraulic retention time (Kadlec and Wallace 2008).…”
Section: Introductionmentioning
confidence: 99%